Pemanfaatan Media Sosial dalam Ekowisata Air Terjun di Sumatera Barat (Sebuah Tinjauan Teoritis) (JURNAL SPASIAL, 2017)
West Sumatra is a province that is around active volcanoes and has high rainfall. This condition forms a waterfall of 29 points or even more. In today's modern era, the functions and roles of social media such as Facebook, Line, Whatsapp, Twitter, and others are very important in providing information about unexplored waterfall ecotourism destinations. This article aims to describe the utilization of social media in disseminating waterfall attractions in West Sumatra. Writing is done based on observations and literature review from various secondary sources. The results of the analysis found several obstacles from the location of ecotourism waterfalls, among others, the absence of supporting tourist attractions, locations that are still difficult to follow, the management is still simple by the surrounding community and lack of security and comfort when tourists visit. This is a challenge for stakeholders in West Sumatra in this case the tourism office, city and district. It takes cooperation between academia, investors, and the community in planning and developing one of the alternative destinations in West Sumatra, namely waterfall ecotourism.